An investigation of the role of N-methyl-diethanolamine in non-aqueous solution for CO2 capture process using 13C NMR spectroscopy. (August 2015) - Chen, Siming; Chen, Shaoyun; Zhang, Yongchun; Chai, Huanhuan; Qin, Liang; Gong, Yutong
Highlights: MDEA cannot take part in the chemical absorption of CO2 in ethanol solution. MDEA involved in the chemical absorption of CO2 with the presence of EMEA in ethanol solution. MDEA cannot help to improve the regeneration efficiency of EMEA. The carbon containing species originated from EMEA and ethanol carboxylation. Abstract: CO2 absorption (at 313 K) and desorption (at 363 K) in 15 wt% N -methyl-diethanolamine (MDEA) + 25 wt% N -ethylmonoethanolamine (EMEA) + 60 wt% ethanol and 25 wt% EMEA + 75 wt% ethanol were investigated in order to determine the role of MDEA in non-aqueous solution for CO2 absorption and EMEA regeneration. The equilibrium solubility of CO2 in 15 wt% MDEA + EMEA + ethanol with different EMEA concentrations (0–25 wt%) was studied in a vapor–liquid equilibrium (VLE) apparatus at 313 K to investigate the effect of the concentration of MDEA and EMEA on the CO2 capture ability in different pressure ranges. The experimental results indicated that the presence of MDEA in EMEA + ethanol can slightly improve the capacity of CO2 due to the deprotonation of EMEA + COO − by MDEA; however, it did not contribute to the improvement of the EMEA regeneration efficiency. The equilibrium solubility of CO2 increased with increasing EMEA concentration below 150 kPa, however, at higher pressure the solution with low EMEA concentration seems to be more beneficial for CO2 scrubbing. Results of 13 C NMR and 1 H– 13 C HMBC spectroscopy confirmed that the carbon containing species after CO2 absorption in MDEA + EMEA + ethanol and EMEA + ethanol solutions originated from the carboxylation reaction of EMEA and ethanol.